RARE CASE OF BLAND WHITE-GARLAND SYNDROME WITH MYOCARDIAL INFARCTION IN PAEDIATRICS - Saleem, Munnaza; Shah, Syed Sajid Hussain; Mehmood, Tahir (Journal of Ayub Medical College Abbottabad, 2013)
A 3.5 months old female infant presented with acute history of loose motions, fever and irritability for 5 days. The infant had history of respiratory distress since birth that exaggerated while feeding along with sweating and increased milk intake. Patient had poor weight gain. On investigations she was found to have anomalous origin of the left coronary artery from the left pulmonary artery (ALCAPA) with dilated cardiomyopathy and anterior wall myocardial infarction which is a very rare diagnosis in paediatrics and very rare condition diagnosed in our settings. Keywords: Anomalous origin, coronary artery, myocardial infarction.